Sukces w wymiarze jednostkowym i jako efekt współpracy z innymi, czyli o potrzebie wsparcia społecznego - Wiśniewska, Danuta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Human functioning in the modern world has a variety of opportunities for achievement a success. Taking different forms of activity, due to the desired result, it can subjectively achieve success. In their efforts a man may need support from others to succeed. The first part of the article shows the different ways of defining success and the characteristics of a successful man. The following section focuses on the types of social support. The third part presents the areas where support is necessary for success.
Keywords: człowiek sukcesu; doradztwo; gap year; koncepcja Work Life Balance; sukces; wsparcie społeczne